Analisis Kompetensi Guru yang Sudah Tersertifikasi melalui Pendidikan dan Latihan Profesi Guru (PLPG) pada Pembelajaran IPA Sekolah Dasar - Kennedy, John; Sa'ud, Udin Syaefudin; Witarsa, Ramdhan (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2023)
Teacher competence is the ability of teachers consisting of personal, social, pedagogic, and professional abilities related to the profession they carry. This teacher competency is measured through a teacher certification program. Teacher certificates can be obtained in several ways, depending on the year the teacher was certified. This study aims to describe the competence of teachers who have been certified through professional teacher education and training, especially in learning natural sciences in primary schools. The method used in this study is a qualitative descriptive method. This method has three stages, namely: the description stage, the reduction stage, and the selection stage. The research data sources are seven teachers who have been certified through education and professional training for teachers. Data collection techniques used are documentation and observation. The research instrument used was a lesson plan document that had been made by the teacher and an observation sheet on the implementation of natural science learning carried out by the teacher in the classroom. The results of the study can show that teachers who are certified through professional teacher education and training have competence in making lesson plans and implementing natural science learning in the sufficient criteria. Therefore, this research can be used as a reference in maintaining the competence of certified teachers through professional teacher education and training by making lesson plans and assessing their abilities when carrying out classroom learning. The competence of certified teachers needs to be maintained regularly.